QUO VADIS PERPOLISIAN KOMUNITAS? (COMMUNITY POLICING) - Agus Pramono (Faculty of Law, Universitas Diponegoro, 2011)
Community policing is an approach whereby the police is actively engaging the community it setves. The scope of community policing may include efforts related to minimizing crime rate, transnational crimes. a rug trafficking, and compliance of laws community